PENGARUH SERVICE RECOVERY, FASILITAS, DAN KOMUNIKASI INTERPERSONAL TERHADAP KEPUASAN MASYARAKAT PADA PELAYANAN DI MAL PELAYANAN PUBLIK BANJARNEGARA - Wahyu Indarti, Westi; lustono, Lustono; Maesaroh, Siti (Medikonis, 2025)
ABSTRACT This study to analyze the influence of service recovery, facilities, and interpersonal communication on public satisfaction with the services provided by the Public Service Mall (MPP) in Banjarnegara. The MPP Banjarnegara is one of the regional government’s innovations to simplify and improve public access to administrative services. However, there are still various public complaints regarding the gap between expectations and the actual services received. This research employs a quantitative approach with a survey method. The sample consists of 99 respondents who are service users at the MPP Banjarnegara. Data were collected using a closed-ended questionnaire. The data analysis techniques used include validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), t-test, F-test, and the coefficient of determination (R²). The results show that service recovery, facilities, and interpersonal communication have a positive and significant influence on public satisfaction, both partially and simultaneously. The coefficient of determination (R²) value of 0.875 indicates that 87,5 percent of the variation in public satisfaction can be explained by the three independent variables. The remaining 12,5 percent is influenced by other factors outside the research model. This study recommends that the MPP Banjarnegara improve the quality of service recovery, provide more adequate facilities, and optimize staff interpersonal communication to enhance public satisfaction with public services.